2005
DOI: 10.1088/0957-0233/16/2/008
|View full text |Cite
|
Sign up to set email alerts
|

Precise measurement of density and structure of undercooled molten silicon by using synchrotron radiation combined with electromagnetic levitation technique

Abstract: X-ray diffraction and density measurements have been simultaneously performed to investigate the atomic structure of molten silicon in a wide temperature range including the undercooling region by using the electromagnetic levitation technique. The density was obtained from the mass and the shape of a levitated sample by a non-contact method based on the image analysis technique. X-ray diffraction experiments were performed by using the synchrotron radiation at SPring8, Japan. From structural analysis of under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
33
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 13 publications
6
33
0
Order By: Relevance
“…This ab initio (plane wave DFT) study has shown that N c is indeed constant after supercooling down to $1400 K, as found experimentally by Kim et al [280] and Higuchi et al [281]. However, the calculations have also shown that N c begins to decrease below $1200 K, the temperature at which the density maximum occurs [287] (Fig.…”
Section: Liquid Si and Ge (L-si And L-ge)supporting
confidence: 69%
“…This ab initio (plane wave DFT) study has shown that N c is indeed constant after supercooling down to $1400 K, as found experimentally by Kim et al [280] and Higuchi et al [281]. However, the calculations have also shown that N c begins to decrease below $1200 K, the temperature at which the density maximum occurs [287] (Fig.…”
Section: Liquid Si and Ge (L-si And L-ge)supporting
confidence: 69%
“…For example, x-ray measurements made using conical nozzle levitation [7,8] have provided structural information for a supercooling of 230 K below the melting point (T M 1685 K) and identified a decrease in the coordination number from 6.3 at 1767 K to about 5.6 at 1458 K. This result is consistent with the predicted decrease in coordination number obtained from simulations using the SW potential as the temperature is reduced below T M , and was argued to provide strong evidence for the existence of an underlying first-order L-L transition. However, other x-ray measurements by Kimura et al [9] employing electromagnetic levitation (EML) for a supercooling of 290 K below the melting point found an increase in the average coordination number from 5.5 at 1793 K to 6.1 at 1403 K. Recent measurements by Higuchi et al [10], using EML to a supercooling of 150 K, found no change in coordination number with temperature, but obtained a rather low value for the coordination number (N 5) relative to previous investigations. The discrepancies between these results and the fact that none of the groups found evidence of a discontinuous change in the structure, indicative of a first-order L-L transition, leaves the matter of a L-L transition in supercooled liquid silicon an open question.…”
mentioning
confidence: 95%
“…First, through the use of high-energy x rays (125 keV), the experiments are performed in a transmission geometry ensuring that the volume structure is probed. The use of high-energy x rays also minimizes data corrections due to sample absorption and multiple scattering required for lower energy measurements [10]. Second, a distinct advantage of ESL over electromagnetic and aerodynamic levitation is that even for nonmetallic samples, the processes of heating and positioning are decoupled, obviating the need for cooling or levitating gases.…”
mentioning
confidence: 99%
See 2 more Smart Citations